Angiogenesis and Microcirculation in Ischemic Heart Disease - Akram, Muhammad; Ghazwani, Eisa Yazeed; Umaru, Isaac John (African Journal of Medicine, Surgery and Public Health Research, 2024)
Angiogenesis among the functional organ systems, the cardiovascular system is the paramount appearing system in the development of vertebrate embryo. However, different epigenetic and genetic mechanisms play important role in the development of vascular organ system. During embryonic life, the blood capillaries from endothelial tissues differentiate from mesodermal cells in the form of vasculo-genesis. Alteration of primary blood vessels into supplementary vascular system is believed to happen through a process known as angiogenesis. The process of angiogenesis happens naturally during pregnancy, wound healing, female menstrual cycle and important in tissue growth and repair. Different pathological conditions like diabetes, chronic kidney disease, cutaneous complications, cancer, neurodegenerative disorders, rheumatoid arthritis and age-related macular degeneration are considered by excessive angiogenesis in which vessels grow in unmannered and unrestricted pattern.